Prediction of power generation of two 30 kW Horizontal Axis Wind Turbines with Gaussian model. (15th September 2021) - Li, Qing'an; Cai, Chang; Kamada, Yasunari; Maeda, Takao; Hiromori, Yuto; Zhou, Shuni; Xu, Jianzhong
Abstract: In order to improve the total efficiency of power generation in a wind farm, this paper investigated the effect of different operating conditions of the upstream wind turbine on the power of the downstream wind turbine by Gaussian wake model. A three-bladed Horizontal Axis Wind Turbine with the generator capacity of 30 kW was used. Firstly, Gaussian model for evaluating the wake flow was developed, which fit well with experiment data. Then, the influence of the operating condition of the upstream turbine on the downstream turbine performance was estimated by calculating the energy amount resulted from the velocity deficit of the wake. Finally, the effect of the installation position of the downstream wind turbine was analyzed. In consequence, the total power coefficient P total of the wind turbines was relatively higher when the upstream turbine was at tip speed ratio λ = 6.4 and pitch angle β = 2° among different test conditions. Meanwhile, the P total showed the maximum value when the downstream turbine was installed at the streamwise location x/D = 2.0 and lateral offset location y/R = 1.5 when the inflow turbulence intensity is 0.22≤ TI ref ≤ 0.35. This paper provided a better guidance for optimizing the wind turbine layout and improving the total power output of the entire wind farm. Highlights: Total power output of the two wind turbines were investigated with Gaussian model. Operating condition of upstream wind turbine on the power output of downstream turbine was estimated. Gaussian model was suggested based on field measurement. Total power output of the two wind turbines of maximum was 0.521 at x/D = 2.0 and y/R = 1.5. Total power output increased when the downstream wind turbine moved to the positive direction of y.